2021
DOI: 10.1101/2021.04.28.21256122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody response to SARS-CoV-2 infection over six months among Nicaraguan outpatients

Abstract: New information is emerging about SARS-CoV-2 epidemiology and immunity, but little of this information comes from low- and middle-income countries or from patients receiving care in the outpatient setting. The current study investigated the SARS-CoV-2 infection status and antibody responses in 157 patients seeking care for a respiratory disease suggestive of COVID-19 in private healthcare clinics during the first wave (June-October 2020) of infections in Nicaragua. We examined nasal swabs for the presence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…A study of outpatients seeking care for acute respiratory disease during the first epidemic wave of SARS-CoV-2 in León showed that 38% had an acute mild COVID-19 infection. 19 A recent cross-sectional study of Nicaraguan health care workers (HCWs) conducted over one month found that 30% of participants had active SARS-CoV-2 infection based on amplification of the SARS-CoV-2 RNA in saliva samples. When accounting for resolved infections in which virus would not be detected, it is likely that SARS-CoV-2 seroprevalence among HCWs is even higher than the infection prevalence, suggesting that seroprevalence among Nicaraguan health care workers is likely higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A study of outpatients seeking care for acute respiratory disease during the first epidemic wave of SARS-CoV-2 in León showed that 38% had an acute mild COVID-19 infection. 19 A recent cross-sectional study of Nicaraguan health care workers (HCWs) conducted over one month found that 30% of participants had active SARS-CoV-2 infection based on amplification of the SARS-CoV-2 RNA in saliva samples. When accounting for resolved infections in which virus would not be detected, it is likely that SARS-CoV-2 seroprevalence among HCWs is even higher than the infection prevalence, suggesting that seroprevalence among Nicaraguan health care workers is likely higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%